Body memories: goddesses of Nusantara, rings of fire and narratives of myth - Candraningrum, Dewi (Yayasan Jurnal Perempuan (YJP), 2014)
Under keningar trees, the bulls drink no more, myth of mother Merapi / Dewi Candraningrum -- Goddess, corporeality, and nature, study of the spirituality of ecofeminism / Gadis Arivia -- Bui Hangi a deity's human wife, analysis of a myth from pura eastern Indonesia / Susanne Rodemeier -- Goddesses of Veda, body, earth, and humankind / Saraswati Dewi -- The trapped goddesses, myth of mother, earth, and nation / Sylvia Tiwon -- Practical theological approach to ecofeminism, story of women, faith, and earth-advocacy / Joyce Ann Mercer -- Integrating Islam and ecofeminism, a monotheistic approach to earth crisis / Muhammad Ali -- Disaster of development, how women's empowerment projects are damaging Indonesian smallholder farming, rural families, and the environment / Laine Berman -- Save the earth from home, women in green commercial discourse in Indonesia / Ratna Noviani -- Tension of private and public spheres in ecological preservation, state, business, and adat women / Donny Danardono -- Protecting women's domestic area & environment, study on eco-friendly batik / Arianti Ina Restiani Hunga